The Impact Of Cultural Diversity On Project Management In An International Organization - Rahal, Farah (جامعة الوادي - University of Eloued, 2021)
Contemporary technology has revealed a number of sophisticated means of communication and transportation. These means have had a radical upheaval on the whole world. The rise of the economic world has been achieved by this globalization. Also, she it has witnessed a dramatic increase in multinational transactions and cooperations, which have made the emergence of what is called cross-cultural business or the multicultural business. International projects are among the manifestations of globalization, where cultural diversity has a major impact on staff because they have distinct perceptions. This is a big challenge for both managers and employees, they have to adapt with multiculturalism, and build a successful multicultural team carrying out a new style of management which is intercultural management. Our research has been emphasized through a case study about a project management in an Italian company located in Algeria, where multiculturalism exists.
مقال
Keywords: Globalization ; Cross-cultural business ; International projects ; Cultural diversity ; Intercultural management